Clonagem e expressão da glicoproteína transmembrana do retrovírus HTLV-1 em células de mamíferos - Penteado, Flora Cristina Lobo [UNESP]; Medeiros, Luciene; Delgado Orellana, Maristela; Palma, Patricia; Fontes, Aparecida Maria; Takayanagui, Osvaldo Massaiti; Covas, Dimas Tadeu (FapUNIFESP (SciELO), 2006)
The retrovirus HTLV-1 is the etiological agent of the adult T-cell leukemia and HTLV-1 associated myelopathy/tropical spastic paraparesis. The proviral genome has 9,032 base pairs, showing regulatory and structural genes. The env gene encodes for the transmembrane glycoprotein gp 21. The development of methodologies for heterologous protein expression, as well as the acquisition of a cellular line that constituently expresses the recombinant, were the main goals of this work. The DNA fragment that encodes for gp 21 was amplified by nested-PCR and cloned into a pCR2.1-TOPO vector. After which, a sub-cloning was realized using the expressing vector pcDNA3.1+. The transfection of mammalian cells HEK 293 was performed transitorily and permanently. Production of the recombinant gp 21 was confirmed by flux cytometry experiments and the cell line producing protein will be used in immunogenicity assays.
Cloning and transmembrane glycoprotein expression of the retrovirus HTLV-1 in mammals' cells
Keywords: Cloning; HTLV-1; Protein expression; Transmembrane glycoprotein; DNA fragment; glycoprotein; membrane protein; recombinant protein; animal cell; cell line; cytometry; envelope gene; gene control; genetic transfection; Human T cell leukemia virus 1; immunogenicity; molecular cloning; nonhuman; polymerase chain reaction; protein blood level; protein expression; Retrovirus; spastic paresis; spinal cord disease; structural gene; T cell leukemia; tropical disease; virus gene; Animals; Cell Lineage; Cloning, Organism; Flow Cytometry; Gene Expression Regulation, Developmental; Human T-lymphotropic virus 1; Mammals; Membrane Glycoproteins; Polymerase Chain Reaction; Viral Envelope Proteins; Animalia; Mammalia